Noncontiguous finished genome sequence and description of Virgibacillus massiliensis sp. nov., a moderately halophilic bacterium isolated from human gut. (November 2015) - Khelaifia, S.; Croce, O.; Lagier, J.-C.; Robert, C.; Couderc, C.; Di Pinto, F.; Davoust, B.; Djossou, F.; Raoult, D.; Fournier, P.-E.
Abstract: Strain Vm-5 T was isolated from the stool specimen of a 10-year-old Amazonian boy. This bacterium is a Gram-positive, strictly aerobic rod, motile by a polar flagellum. Here we describe its phenotypic characteristics and complete genome sequence. The 4 353 177 bp long genome exhibits a G + C content of 36.87% and contains 4394 protein-coding and 125 predicted RNA genes. Phylogenetically and genetically, strain Vm-c is a member of the genus Virgibacillus but is distinct enough to be classified as a new species. We propose the creation of V. massiliensis sp. nov., whose type strain is strain Vm-5 T (CSUR P971 = DSM 28587).